Maternal and Neonatal Serum Zinc Level and Its Relationship with Neural Tube Defects - Dey, Arjun Chandra; Shahidullah, Mohammod; Mannan, Mohammad Abdul; Noor, Mohammad Khaled; Saha, Laxmi; Rahman, Shahana A (Journal of Health, Population and Nutrition, 2010)
Neural tube defect (NTD) is a multi-factorial disorder in which nutritional, genetic and environmental factors are involved. Among the nutritional factors, low level of serum zinc has been reported from different parts of the world. This hospital-based case-control study was conducted with the objective of finding the relationship between serum zinc level in newborns and their mothers and NTDs in a Bangladeshi population. The study was conducted during August 2006-July 2007 at the Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka. In total, 32 mothers and their newborns with NTDs were included as cases and another 32 mothers with their normal babies were included as controls. Concentration of serum zinc was determined by pyro-coated graphite furnace atomic absorption spectrophotometer (GF-AAS). The mean age of the case and control mothers was 25.28 years and 24.34 years respectively. The mean gestational age of the case newborns was 36.59 weeks and that of the control newborns was 37.75 weeks. The mean serum zinc level of the case and control mothers was 610.2 μg/L and 883.0 μg/L respectively (p<0.01). The mean serum zinc level of the case and control newborns was 723 μg/L and 1,046 μg/L respectively (p<0.01). In both case and control groups, the serum zinc level of the newborns positively correlated with that of the mothers. The serum zinc levels of the mothers and newborns negatively correlated with NTDs. Mothers with serum zinc level lower than normal were 7.66 [95% confidence interval (CI) 2.5-23.28] times more likely to have NTDs compared to the normal zinc level of mothers. After adjusting for the zinc level of the newborns, parity, and age of the mothers, this risk reduced 1.61 times [confidence interval (CI) 95% 0.24-8.77]. On the other hand, the low serum zinc level of the newborns was 7.22 times more associated with NTDs compared to the newborns with the normal serum zinc level, which was statistically significant (p=0.001). After adjusting for other factors, such as maternal age and parity, newborns with the low serum zinc level was found to be 9.186 times more likely to be associated with NTDs compared to newborns with normal serum zinc level. Based on the findings, it may be concluded that the low serum zinc levels of newborns may be associated with NTDs. To confirm these findings, a further study with a larger sample-size is recommended. Moreover, a follow-up study with zinc supplementation to pregnant women and its impact on NTDs is also recommended. Key words: Atomic absorption spectrophotometer; Case-control studies; Neural tube defects; Serum zinc; Zinc deficiency; Bangladesh DOI: 10.3329/jhpn.v28i4.6040 J HEALTH POPUL NUTR 2010 Aug;28(4):343-350